Towards a Self-Reliant India: Closing the Saving Investment Gap (Global Journal of Human-Social Science, 2024)
For a developing country such as India where the growth potential is high and the scope for poverty reduction is also significant a policy that lifts the poor out of poverty by expanding the overall pie is preferable because redistribution is only feasible if the size of the economic pie grows rapidly Therefore achieving economic growth requires the government to adopt different types of policies such as promoting savings stimulating investment and increasing internal production Rasmidatta 2011 Present piece of the study is an endeavor to find out the volume of gap between savings investments in India and ways to reduce it up to zero size so that not only the burden of interest payment could be done away with simultaneously growth process can be made sustainable in the long -run without sacrificing our sovereignty to external world In a nutshell growth process must be inner-engineered as the growth of individual Decoupling or complete detachment from external world is essential for lasting happiness Bhagwad Geeta or welfare both for the individual and the economy